La recaudación del impuesto predial urbano y su incidencia en la gestión presupuestaria del GADM del cantón Penipe, período 2018. - Silvia Viviana, Carranza Haro (2020)
The Municipal Governments are entities that enjoy fiscal, political and administrative autonomy, within the parameters that have been determined by the Constitution and by each of the decentralization laws that exist in the country, their main purpose is to carry out works that help meet the needs of the population and cantonal development. This research "The collection of urban property tax and its impact on the budgetary management of the GADM of the canton Penipe, period 2018", was carried out with the purpose of knowing based on which they prepare a budget and how it is handled, in the same way, give the conditions that justify the importance of the research and the objectives that the development of the present study allows us with its respective hypothesis. The State of Art included the background of research related to the subject, the collection of the urban property tax of the GADM of Penipe, as well as the theoretical references on the collection, property tax and budget management. The methodology used in the research was based on the deductive, documentary, field and non-experimental method. The study population was made up of the officials who work in the Collection, Financial Department of the GAD Municipal and the users of past due loans, to whom the interview and survey were applied, were the ones who helped us to collect selected information. In the results and discussion, we proceeded to organize the information obtained to carry out the analysis and interpretation, which later helped us to prepare the proposal, conclusions and recommendations that are focused on the results obtained and in order to improve institutional management. Key words: Collection, Urban Property Tax, Budget management.